The Utilization of Digital Social Media in Disseminating the Issue of Multicultural Education to Strengthen the Social Resilience among Adolescents - Effendi, Stephanus Yusuf Tri (KnE Social Sciences, 2019)
This paper examines the importance of multicultural education and how school institution utilizes the digital social media platform as an effort tool to strengthen the social resilience for the adolescent. Indonesia is a plural society state that is built on the multicultural base. The diversity of social groups in Indonesia has the potential for latent and manifest conflicts. The tensions and conflicts occur if there are a fundamental disagreement and values among different groups within plural society. Tensions and conflicts can be suppressed if each group shares the common beliefs and values that allow them to establish broad cooperative relationships. To preserve the spirit of national unity as what became the motto of the Indonesian nation, namely Bhineka Tunggal Ika, and to prevent horizontal conflicts of cultural, religious and ethnic background, then there are some ways that can be done which one of them is through multicultural education since knowledge gives feasibility and hope for the expected of nation. Utilization of the digital social media platform in this information and communication technology (ICT) era would help the education practitioners or institutions in amplifying the multiculturalism notion among adolescents as the instrument in the understanding building. This paper is using descriptive qualitative method and sociology theory of education, particularly in structural functionalist and constructivist perspective, a framework of thinking.